The relationship between employee commitment and employee performance among support staff at Jabatan Kerja Raya (JKR) In Kuching, Sarawak / Alliya Najwa M Idros - M Idros, Alliya Najwa (2018)
Today’s organizations need a commitment within a staff who understand the complexities of the rapidly changing global environment that leads the better organizational performance. The authority to lead not to be located in the person, different organizational culture existed, lack of the commitment attributes and role overload were the dilemmas experienced of performance. The study utilized a correlational quantitative design with 100 support staff at selected departments in Jabatan Kerja Raya (JKR) in Kuching, Sarawak. Thus, the aim of the study is to identify to what extent the commitment practiced by the top management that affect the Employee Commitment as well as examine the Relationship between Employee Commitment and Employee Performance among the Support Staff.